Memories of a future home : diasporic citizenship of Chinese in Panama - Siu, Lok C. D. (Stanford University Press, 2005)
"While the history of Asian migration to Latin America is well documented, we know little about the contemporary experience of diasporic Asians in this part of the world. Memories of a Future Home offers an intimate look at how diasporic Chinese in Panama construct a home and create a sense of belonging as they inhabit the interstices of several cultural-national formations--Panama, their nation of residence; China/Taiwan, their ethnic homeland; and the United States, the colonial force. Juxtaposing the concepts of diaspora and citizenship, this book offers an innovative framework to help us understand how diasporic subjects engage the politics of cultural and political belonging in a transnational context. It does so by examining the interaction between continually shifting geopolitical dynamics, as well as the maneuvers undertaken by diasporic people to negotiate and transform those conditions. In essence, this book explores the contingent citizenship experienced by diasporic Chinese and their efforts to imagine and construct "home" in diaspora."--